Biodiversity of culturable heterotrophic bacteria in the Southern Adriatic Sea Italian coastal waters - Stabili, Loredana; Cavallo, Rosa Anna (Scientia Marina, 2004)
The qualitative and quantitative composition of culturable heterotrophic bacteria in water samples from the Southern Adriatic Sea of Italy was examined. Water samples were collected monthly, for a year, at 16 stations along the coast line between Brindisi and Santa Maria di Leuca. The results obtained described the heterotrophic bacterial community over an annual cycle. Mean values of bacterial densities were 5.3 x 104 CFUml-1 in Brindisi, 5.8 x 104 CFUml-1 in S. Cataldo, 4.3 x 104 CFUml-1 in Otranto and 6.7 x 104 CFUml-1 in S. M. di Leuca. The differences in bacterial densities between the sites considered were estimated. The hydrodynamic circulation, the trophism and the geographical position of the examined sites contribute to justify the different bacterial density trends. The bacterial community consisted mainly of the genera Aeromonas, Pseudomonas, Photobacterium and Flavobacterium. The Enterobacteriaceae represented a considerable fraction of the bacterial community in the Southern Adriatic Sea. Bacilli were predominant among the Gram positive bacteria. The enzymatic versatility of the observed genera suggest their importance in organic matter turnover of this oligotrophic ecosystem.